Nutritional and Lipid Modulation of PCSK9: Effects on Cardiometabolic Risk Factors. Issue 4 (8th February 2017) - Krysa, Jacqueline A; Ooi, Teik Chye; Proctor, Spencer D; Vine, Donna F
Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a serine protease involved in the regulation of LDL receptor (LDLR) expression and apolipoprotein B lipoprotein cholesterol metabolism. Hepatic PCSK9 protein expression, activity, and secretion have been shown to affect cholesterol homeostasis. An upregulation of hepatic PSCK9 protein leads to increased LDLR degradation, resulting in decreased uptake of apoB lipoproteins and a consequent increase in the plasma concentration of these lipoproteins, including LDL and chylomicron remnants. Hence, PCSK9 has become a novel target for lipid-lowering therapies. The aim of this review is to outline current findings on the metabolic and dietary regulation of PCSK9 and effects on cholesterol, apoB lipoprotein metabolism, and cardiovascular disease (CVD) risk. PCSK9 gene and protein expression have been shown to be regulated by metabolic status and the diurnal pattern. In the fasting state, plasma PCSK9 is reduced via modulation of the nuclear transcriptional factors, including sterol regulatory element–binding protein (SREBP) 1c, SREBP2, and hepatocyte nuclear factor 1α. Plasma PCSK9 concentrations are also known to be positively associated with plasma insulin and homeostasis model assessment of insulin resistance, and appear to be regulated by SREBP1c independently of glucose status. Plasma PCSK9 concentrations are stable in response to high-fat or high-protein diets in healthy individuals; however, this response may differ in altered metabolic conditions. Dietary n–3 polyunsaturated fatty acids have been shown to reduce plasma PCSK9 concentration and hepatic PCSK9 mRNA expression, consistent with their lipid-lowering effects, whereas dietary fructose appears to upregulate PCSK9 mRNA expression and plasma PCSK9 concentrations. Further studies are needed to elucidate the mechanisms of how dietary components regulate PCSK9 and effects on cholesterol and apoB lipoprotein metabolism, as well as to delineate the clinical impact of diet on PCSK9 in terms of CVD risk.